Comparative Study Of Islamic Economic Law And The Capitalist - Tesa Mellina; Mohammad Ghozali (Jurnal Ilmiah Al-Syir'ah, 2018)
The implementation ofthe capitalist system has eliminated the Islamic values in economic practice. After the financial crisis hit the world, the capitalist system reaped many questions and its greatnessbegins to be doubted. The capitalist system implementationprecisely creates new problems in the economy. The concept of individualism which is the main key in capitalist practice only creates economic injustice and misery of the poor. The only economic theory that is expected as a light in dealing with economic problems is an economic system that is able to create justice,the welfare of all parties and blessings both the world and the hereafter. The theory is the Islamic economics which in practice is inseparable from Islamiceconomic law. Islamic economic law that underlies the Islamic economic system is totally different from the capitalist economic system.Keywords: Islamic Economic Law; Islamic economics; Capitalist Economy